2022
DOI: 10.3389/frobt.2022.906424
|View full text |Cite
|
Sign up to set email alerts
|

A novel immersive virtual reality environment for the motor rehabilitation of stroke patients: A feasibility study

Abstract: We designed and implemented an immersive virtual reality (VR) environment for upper limb rehabilitation, which possesses several notable features. First, by exploiting modern computer graphics its can present a variety of scenarios that make the rehabilitation routines challenging yet enjoyable for patients, thus enhancing their adherence to the therapy. Second, immersion in a virtual 3D space allows the patients to execute tasks that are closely related to everyday gestures, thus enhancing the transfer of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…While immersed in the virtual environment, the subjects performed three different tasks ( Fregna et al, 2022 ), with the purpose of acting with and paying attention to their virtual body. Task 1 (Glasses): The task started with four pedestals presented on the table.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While immersed in the virtual environment, the subjects performed three different tasks ( Fregna et al, 2022 ), with the purpose of acting with and paying attention to their virtual body. Task 1 (Glasses): The task started with four pedestals presented on the table.…”
Section: Methodsmentioning
confidence: 99%
“…Participants wore a body-tracking suit that provided real-time motion capture, so that they could see their virtual body moving synchronously with their real body. To draw attention to their novel virtual body, we required participants to perform a series of manual tasks ( Fregna et al, 2022 ) during the virtual embodiment.…”
Section: Introductionmentioning
confidence: 99%
“…An essential consideration in the implementation of hand redirection techniques is to ensure that users maintain a strong sense of ownership in the virtual environment [51]. Prior studies have demonstrated that inducing a body ownership illusion during VR rehabilitation can improve the therapeutic effect over the non-embodied rehabilitation in VR [8,24,64]. As such, a key focus in prior research has been on determining the detection thresholds of these offset across various motion axes [20,32,51].…”
Section: Hand Redirection In Vrmentioning
confidence: 99%
“…This suggests that a higher immersion level could induce a stronger brain activity in visual guided MI training. Individual feeling presence in a specific immersive virtual environment (VE) designed for rehabilitation is the unique advantage of VR rehabilitation [13], and virtual body (i.e., the avatar which representing user self) is also presented in recent motor rehabilitation studies [10], [14]- [16]. Sollfrank et al [17] indicated that virtual avatar could be employed to represent the real body in immersive VR, providing end-users with a realistic 3D presentation of limb movements, which seems to help to get a concrete feeling of kinesthetic MI and exerts significant effects on motor cortex activation.…”
Section: Introductionmentioning
confidence: 99%